Investment And Financing Analysis Of Automotive Industry Of China - Song, Wang (2005)
The study of industry life cycle of automotive industry in China shows that the industry is entering a period of consolidation and rationalization. Meanwhile, the analysis of risk companying with the development of automotive industry in China is low which implies that investors are subjected lower risk of their investments of automotive industry in China.